PENGARUH LEADER MEMBER EXCHANGE TERHADAP KOMITMEN ORGANISASI PADA PT MIDIAN KARYA PASURUAN - Amiruddin Prisetyadi (Manajemen Bisnis, 2011)
Fakultas Ekonomi Universitas Muhamadiyah MalangABSTRACTThis study aimed to describe and explain the influence of leader member exchange toorganizational commitment of employees at PT Midian Karya Pasuruan. Data Analysis uses RangeScale and Simple Linear Regression. The results reveal that the Leader Member Exchange (LMX)show very strong and high in Organizational Commitment. Based on statistical tests and empiricalconditions in the company is known that the leader member exchange is one of the factors thatdetermine the commitment of the organization and the organizational commitment of employees.Furthermore, the t test support that the leader member exchange have a significant influence onorganizational commitment. Based on this research, the suggestion is that refers to the responses ofrespondents on the quality of LMX is high, thereby managing the proximity relationship between theboss-subordinate can be done in several ways, the boss can do personal identification on eachemployee. It can be more flexible to subordinates so that subordinates can meet with employers tomore easy exchange ideas. Creativity is not only owned by the in group, but also could be developedin every person (out group) through a process of gradual nature.Keywords : leader member exchange, organization commitment